On the hydration of synthetic aluminosilicate glass as a sole cement precursor. (September 2022) - Alzeer, Mohammad I.M.; Nguyen, Hoang; Fabritius, Tapio; Sreenivasan, Harisankar; Telkki, Ville-Veikko; Kantola, Anu M.; Cheeseman, Christopher; Illikainen, Mirja; Kinnunen, Paivo
Abstract: This paper reports on the synthesis and characteristics of a novel aluminosilicate glass-based cementitious binder. We investigated the hydration kinetics, degree of reaction, and phase assemblage of the glass via XRD, DTG, 27 Al and 29 Si MAS NMR, FTIR, SEM/EDS and thermodynamic modelling. The glass exhibits hydraulic properties in which the binder developed impressive compressive strength at early age. The main hydration products are an intermixed of Na and/or Al incorporated in C–S–H gel. Hydrotalcite precipitated with slower rate and thus may generate crystallization pressure on the binder at late stage. The glass reached a high degree of hydration (ca. 73 % based on quantitative 29 Si NMR analysis) without using any activators or co-binding systems. Therefore, the developed glass reported herein has high potential as a new low-carbon cementitious binder since it can be synthesised from naturally occurring carbonate free silicate minerals. Graphical abstract: Unlabelled Image Highlights: Novel synthetic glass-based cement was developed. The glass is hydraulically reactive without the use of activators or co-binders. The glass could be synthesised with low-raw materials related CO2 emissions. The developed glass has potential as cementitious binder with low carbon footprint.